Implementation of a community health worker-focused team-based model of care: What modifications do clinics make? - Sotelo Guerra, Laura J.; Ortiz, Janette; Liljenquist, Kendra; Szilagyi, Peter G.; Fiscella, Kevin; Porras-Javier, Lorena; Johnson, Gina; Friesema, Lisa; Coker, Tumaini R. (Frontiers in Health Services, 2023)
Background. Team-based care offers potential for integrating non-clinicians, such as Community Health Workers (CHWs), into the primary care team to ensure that patients and families receive culturally-relevant care to address their physical, social, and behavioral health and wellness needs. We describe how two Federally Qualified Health Center (FQHC) organizations adapted an evidence-based, team-based model of well-child care (WCC) designed to ensure that parents of young children, ages 0-3, have their comprehensive preventive care needs met at WCC visits. Methods. Each FQHC formed a Project Working Group composed of clinicians, staff, and parents to determine what adaptations to make in the process of implementation of PARENT (Parent-Focused Redesign for Encounters, Newborns to Toddlers), a team-based care intervention that uses a CHW in the role of a preventive care coach. We use the Framework for Reporting Adaptations and Modifications to Evidence-based interventions (FRAME), to chronicle the various intervention modifications and the adaptation process, focusing on when and how modifications occurred, whether it was planned or unplanned, and reasons and goals for modification. Results. The Project Working Groups adapted several elements of the intervention in response to clinic priorities, workflow, staffing, space, and population need. Modifications were planned and proactive, and were made at the organization, clinic, and individual provider level. Modification decisions were made by the Project Working Group and operationalized by the Project Leadership team; examples of modifications include 1) changing the Parent Coach educational requirement from Master’s degree to bachelor’s degree or equivalent experience to reflect needs of Coach role, 2) use of FQHC-specific templates for the Coach’s documentation of the pre-visit screening in the EHR, and 3) use of electronic social needs referral tools to help the Coach track and follow up on social need referrals. The modifications did not change the core elements (i.e., parent coach provision of preventive care services) or intervention goals. Conclusions. For clinics implementing team-based care interventions, engagement of key clinical stakeholders early and often in the intervention adaptation and implementation process, and planning for intervention modifications at both at an organizational level and at a clinical level are critical for local implementation.